Principles of corporate finance - Brealey, Richard A. (McGraw-Hill/Irwin series in finance, insurance, and real estate., 2020)
"ISBN: 9781260565553 is an International Student Edition of Principles of Corporate Finance 13th Edition by: Richard A Brealey, Stewart C Myers and Franklin Allen This ISBN is Textbook only. It will not come with online access code. The content of of this title on all formats are the same. Brealey, Principles of Corporate Finance, 13e, describes the theory and practice of corporate finance" -- Amazon.